2016
DOI: 10.1016/j.neulet.2016.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Disinhibition-like behavior in a P301S mutant tau transgenic mouse model of frontotemporal dementia

Abstract: Frontotemporal dementia (FTD) presents clinically with behavioral changes including disinhibition. Mutations in the tau-encoding MAPT gene identified in familial cases of FTD have been used to generate transgenic mouse models of the human condition. Here, we report behavioral changes in a recently developed P301S mutant tau transgenic mouse, including disinhibition-like behavior in the elevated plus maze and hyperactivity in the open field arena. Furthermore, histological analysis revealed the amygdala as a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 26 publications
8
41
0
Order By: Relevance
“…They also show signs of a mild decrease in anxiety in the elevated plus maze test, which some authors interpret as disinhibition and might indicate alterations in amygdala or prefrontal cortex function (Roberson, 2012; Koss et al, 2016). These phenotypes are consistent with those observed in other FTD mouse models (Takeuchi et al, 2011; Przybyla et al, 2016; Vernay et al, 2016a), although in some FTD models an increase in anxiety was also reported (Koss et al, 2016; Liu et al, 2016). Further analysis are required to clearly define if some form of disinhibition is present in tTA/WT12 mice.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…They also show signs of a mild decrease in anxiety in the elevated plus maze test, which some authors interpret as disinhibition and might indicate alterations in amygdala or prefrontal cortex function (Roberson, 2012; Koss et al, 2016). These phenotypes are consistent with those observed in other FTD mouse models (Takeuchi et al, 2011; Przybyla et al, 2016; Vernay et al, 2016a), although in some FTD models an increase in anxiety was also reported (Koss et al, 2016; Liu et al, 2016). Further analysis are required to clearly define if some form of disinhibition is present in tTA/WT12 mice.…”
Section: Discussionsupporting
confidence: 89%
“…These data argues against an unspecific effect on non-motor behaviors due to increased anxiety or impaired visual function. Additionally, they suggest that TDP-43-WT mice may show disinhibition, as reported in other mouse models for FTD (Yin et al, 2010; Ke et al, 2015; Przybyla et al, 2016). …”
Section: Resultssupporting
confidence: 56%
“…In the elevated O‐maze transgenic mice also spent more time exploring the open arm. Short latency time to exit from the dark compartment is a parameter that reflecting impulsivity and the increased exploratory interest in the light compartments is an indicator of decreased anxiety, which could be interpreted as excessive risk‐taking behaviour and/or disinhibition or even emotional dysfunction, which are often observed in FTLD patients …”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] ments is an indicator of decreased anxiety, which could be interpreted as excessive risk-taking behaviour and/or disinhibition or even emotional dysfunction, which are often observed in FTLD patients. 28 The development of a memory deficit is not uncommon in FTLD patients and therefore we studied formation of memory in L-FUS mice using the extinction fear conditioning test. In mice, freezing in response to an adverse stimulus, like an electric shock used in this test, reflects their formation of memory to the context.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…These findings are not universal, however. Increased time in the open arms of an elevated plus-maze is observed in certain Grn- deficient mutants (42), tau-encoding MAPT transgenics (46,47) as well as the CamKIIa-driven CHMP2B model (38). Yet a different Grn- deficient mutant (43) and the recently described PLB tau model – a mutant that expresses a single copy of human FTD-associated mutant tau – both show heightened anxiety (48).…”
Section: Discussionmentioning
confidence: 99%